The impact of formulation variables on the optimization of pilot scale clobetasol 17-propionate creams. Issue 1 (1st January 2020) - Fauzee, Ayeshah Fateemah Beebee; Walker, Roderick Bryan
Abstract: The impact of formulation variables on the optimization of pilot scale clobetasol 17-propionate (CP) cream formulations was investigated using a Central Composite Design of Experiments. Thirty batches of cream were manufactured and the formulation variables assessed were % v/v propylene glycol, % w/w Gelot® 64, cetostearyl alcohol and glyceryl monostearate content. The responses monitored included viscosity, spreadability, pH, CP content, extrudability, electrical conductivity, and % CP released at 72 hours. The responses were compared to those of a reference product, Dermovate® cream. ANOVA analysis revealed that viscosity, spreadability, and % CP released at 72 hours were significant formulation responses (p < 0.05). Cetostearyl alcohol had the greatest impact on quality of pilot scale products. An increase in cetostearyl alcohol resulted in an increase in viscosity, a decrease in spreadability, and a decrease in % CP released at 72 hours. The optimized pilot scale CP formulation contained 46% v/v propylene glycol, 8.6% w/w cetostearyl alcohol, 10.5% w/w glyceryl monostearate, and 3.8% w/w Gelot® 64. The resultant viscosity, spreadability, pH, CP content, extrudability, electrical conductivity, and % CP released were 44633cP, 24.91cm 2, 101.23 %, 76.98 g/cm 2, 198.23 µS/cm, and 50.23%. The addition of cetostearyl alcohol and Gelot® 64 is critical for establishing a soft formulation that leads to the formation of a mixed crystal bilayer network of high viscosity. The formation of a separate crystalline lipophilic network usually occurs in semi-solid formulations that contain high concentrations of emulsifier, leading to an increase in shear stress and greater physicochemical stability of the formulation. The use of experimental design approaches to formulation development activities, permit evaluation of multiple factors simultaneously, reducing the time and costs asscoiated with product development activities, whilst identifying a composition design space and ensuring stable and effective dosage forms are produced.